Myeloid cannabinoid CB1 receptor deletion confers atheroprotection in male mice by reducing macrophage proliferation in a sex-dependent manner - Wang, Yong; Li, Guo; Chen, Bingni; Shakir, George; Volz, Mario; Vorst, Emiel P. C. van der; Maas, Sanne L; Geiger, Martina; Jethwa, Carolin; Bartelt, Alexander; Li, Zhaolong; Wettich, Justus; et al. (Cardiovascular research, 2024)
Although the cannabinoid CB1 receptor has been implicated in atherosclerosis, its cell-specific effects in this disease are not well understood. To address this, we generated a transgenic mouse model to study the role of myeloid CB1 signalling in atherosclerosis.Here, we report that male mice with myeloid-specific Cnr1 deficiency on atherogenic background developed smaller lesions and necrotic cores than controls, while only minor genotype differences were observed in females. Male Cnr1-deficient mice showed reduced arterial monocyte recruitment and macrophage proliferation with less inflammatory phenotype. The sex-specific differences in proliferation were dependent on oestrogen receptor (ER)α-oestradiol signalling. Kinase activity profiling identified a CB1-dependent regulation of p53 and cyclin-dependent kinases. Transcriptomic profiling further revealed chromatin modifications, mRNA processing, and mitochondrial respiration among the key processes affected by CB1 signalling, which was supported by metabolic flux assays. Chronic administration of the peripherally restricted CB1 antagonist JD5037 inhibited plaque progression and macrophage proliferation, but only in male mice. Finally, CNR1 expression was detectable in human carotid endarterectomy plaques and inversely correlated with proliferation, oxidative metabolism, and inflammatory markers, suggesting a possible implication of CB1-dependent regulation in human pathophysiology.Impaired macrophage CB1 signalling is atheroprotective by limiting their arterial recruitment, proliferation, and inflammatory reprogramming in male mice. The importance of macrophage CB1 signalling appears to be sex-dependent.